Exposure therapy tailored to inhibitory learning principles in a naturalistic setting: an open pilot trial in obsessive-compulsive outpatient care - Kühne, Franziska; Hobrecker, Lea Kathrin; Heinze, Peter Eric; Meißner, Claudia; Weck, Florian (Frontiers in Psychology, 2024)
Inhibitory learning (IL) theory offers promising therapeutic strategies. However, more evidence, especially regarding OCD treatment in routine care, is needed. The present pilot study investigated the positive and negative effects of IL-focused cognitive-behavioral therapy (CBT) in a university outpatient setting. A total of N = 21 patients (57.14% male, mean age 31.14, SD = 12.39 years) passed through manualized therapy delivered by licensed psychotherapists. Between the first and 20th IL-focused CBT session, obsessive-compulsive symptoms (Obsessive Compulsive Inventory-Revised, d = 3.71), obsessive beliefs (Obsessive-Beliefs Questionnaire, d = 1.17), depressive symptoms (Beck Depression Inventory, d = 3.49) and overall psychological distress (Global Severity Index, d = 3.40) decreased significantly (all ps <.01). However, individual patients reported negative effects of therapy. The results underline the value of thorough investigations of novel therapeutic interventions in naturalistic settings.